Modelos matemáticos para problemas de dimensionamento de lotes com restrições de capacidade e custos de transporte - Morabito, Reinaldo; De Araujo, Silvio Alexandre; Molina, Flavio [UNESP] (FapUNIFESP (SciELO), 2013)
In this paper, capacitated lot sizing problems in which the classical lot sizing decisions are made considering the transportation costs of the manufactured products were studied. These costs are related to the necessary number of pallets or trucks to pack and/or transport the products from the factory to the warehouse. Three extensions of a mixed integer linear programming model from the literature are considered, representing general cases that are commonly found in companies. These models are tested and evaluated using an optimization package, and a Lagrangian heuristic was developed for one of the extensions proposed.
Mathematical models for capacitated lot sizing problems with transportation costs
Keywords: Integer mixed programming; Lot sizing; Transportation cost